The Role of Human Resources, Hardware, and Databases in Mass Media Companies - Saputra, Farhan; Nofrialdi, Reski (Green Publisher, 2022)
The Management Information System, which includes Human Resources, Network, and Database, currently has a vital role in achieving the company's goals and sustainability. The information obtained will be processed into data and used for a company's decision-making. Companies engaged in the field of Media and Communication are also very closely related to the above variables, which help determine their company's sustainability. Therefore, it is necessary to understand Management Information Systems, especially Human Resources, Hardware, and Databases, to create effective, quality, and valuable information for the company. The purpose of writing this article is to describe the variables above. The results are: 1) The Role of Human Resources in Mass Media Companies, 2) Hardware in Mass Media Companies, 3) Databases in Mass Media Companies.